Ethical Collection, Storage, and Use of Public Health Data: A Proposal for a National Privacy Protection - Lee, Lisa M; Gostin, Lawrence O (JAMA : the journal of the American Medical Association, 2009)
Public health agencies at all levels--locals, state, and federal--collect, store, and use personal health and behavior data to meet their legal obligation to identify and control health threats or evaluate and improve public health programs or services. The foundation for this collection of health data is public trust, which requires maintaining the privacy and security of sensitive information. Despite its critical importance, there is no national standard for safeguarding data held by public health agencies. Instead, privacy safeguards are fragmented across 50 states, creating uncertain and inconsistent privacy protection. Here, Lee and Gostin comment on the current debate by the US Congress on privacy standards of medical health records.